New Trends in Medical and Service Robots Design, Analysis and Control (Mechanisms and Machine Science,, 2018)
These are selected papers presented at the 5th International Workshop on Medical and Service Robots (MESROB 2016). The main topics of the workshop included: Exoskeleton and prostheses; Therapeutic robots and rehabilitation; Cognitive robots; Humanoid & Service robots; Assistive robots and elderly assistance; Surgical robots; Human-robot interfaces; Kinematic and mechatronic design for medical and assistive robotics; and Legal issues in medical robotics. The workshop brought together researchers and practitioners to discuss new and emerging topics of Medical and Service Robotics. The meeting took place at castle St. Martin in Graz, Austria, from 4-6 July, 2016. .